British and American Exchange Policies: II. The American Experience - Harris, S. E. (Quarterly Journal of Economics, 1934)
1. Exchange Policy, 1933–34, 686. — 2. Gold Buying and Exchange Depreciation, 690. — 3. Exchanges, Prices and Economic Conditions, 1933–34, 696. — 4. Economic Conditions Here and Elsewhere, 1933, 698. — 5. Exchange Depreciation and Prices of International Commodities, 700. — 6. Exchange Depreciation and Farm Prices, 709. — 7. Sectional Price Movements, 714. — 8. Depreciation and the Balance of Payments, 716. — 9. The Balance of Trade and Depreciation, 718. — 10. Conclusion, 722